Interactions Between the Prefrontal Cortex and Amygdala During Delay Discounting and Reversal. - Churchwell, John C.; Morris, Andrea M.; Heurtelou, Nila M. (Behavioral Neuroscience, 2009)
Interactions between the prefrontal cortex and amygdala are thought to be critical for reward anticipation. Alterations in reward anticipation that lead to an inability to wait for rewards or a diminished capacity to change behavior when doing so would be optimal are often termed impulsivity and compulsivity, respectively. Distinct regions of the prefrontal cortex may support decreased impulsivity through self-control and decreased compulsivity through flexibility. However, both self-control and flexibility appear to involve the amygdala. Using a delay discounting paradigm, the current investigation found that inactivation and disconnection of the medial prefrontal cortex and basolateral amygdala led rats to become more impulsive by affecting preference for smaller immediate over larger delayed rewards. Conversely, inactivation and disconnection of the orbitofrontal cortex and amygdala led rats to become more compulsive as demonstrated by an inability to flexibly reverse stimulus-reward relationships in an odor reversal task. The current findings support a double dissociation between orbitofrontal cortex-amygdala interactions for odor reversal and medial prefrontal cortex-amygdala interactions for delay discounting. Reprinted by permission of the publisher.